Use of Technetium‐99m‐Pyrophosphate Single‐Photon Emission Computed Tomography/Computed Tomography in Monitoring Therapeutic Changes of Eplontersen in Patients With Hereditary Transthyretin Amyloid Cardiomyopathy - Yu, An‐Li; Chen, Yi‐Chieh; Tsai, Cheng‐Hsuan; Wu, Yuan‐Kun Aden; Su, Mao‐Yuan; Chou, Chia‐Hung; Shun, Chia‐Tung; Hsueh, Hsueh‐Wen; Juang, Jimmy Jyh‐Ming; Lee, Ming‐Jen; Tseng, Ping‐Huei; Hsu, Chia‐Hua; et al. (Journal of the American Heart Association, 2024)
Hereditary transthyretin amyloid cardiomyopathy (hATTR-CM) is a progressive and fatal disease. Recent evidence indicates that bone scintigraphy may serve as a tool to monitor the effectiveness of hATTR-CM treatment. The objective of this study was to examine how eplontersen therapy influences the semiquantitative uptake of technetium-99m-pyrophosphate in individuals diagnosed with hATTR-CM. We retrospectively analyzed a prospective cohort from the NEURO-TTRansform trial, including patients with hATTR-CM receiving eplontersen (45 mg/4 weeks). A control group comprised patients with hATTR-CM who had not received eplontersen, inotersen, tafamidis, or patisiran. Technetium-99m-pyrophosphate single-photon emission computed tomography/computed tomography was conducted at baseline and during follow-up. Thirteen patients with hATTR-CM were enrolled, with 6 receiving eplontersen and 7 serving as the control group. The median follow-up time was 544 days. The eplontersen group exhibited a significant decrease in volumetric heart and lung ratio (3.774 to 2.979, =0.028), whereas the control group showed no significant change (4.079 to 3.915, =0.237). Patients receiving eplontersen demonstrated a significantly greater reduction in volumetric heart and lung ratio compared with the control group (-20.7% versus -3.4%, =0.007). The volumetric heart and lung ratio used to quantify technetium-99m-pyrophosphate uptake showed a significant reduction subsequent to eplontersen treatment in individuals diagnosed with hATTR-CM. These findings suggest the potential efficacy of eplontersen in treating hATTR-CM and highlight the value of technetium-99m-pyrophosphate single-photon emission computed tomography/computed tomography as a tool for monitoring therapeutic effectiveness.